Contextual predictors of child fatality and near fatality cases due to abuse and neglect. (27th February 2022) - Garcia, Antonio R.; Ibekwe‐Okafor, Nneka; Wasch, Sarah; Kim, Minseop
Abstract: Little is known about what factors predict fatality and near fatality (NF) involving child maltreatment and if predictors differ between them. Analyses of cases in 2017 and 2018 in one Mid‐Atlantic state revealed that prior child welfare history and prevalence of risk factors, such as substance abuse, mental illness, interpersonal violence, chronic abuse, incarceration, sibling injuries, and unstable housing did not differ between fatality and NF cases. Logistic regression revealed fatalities decreased by 78% if victims received Emergency Room treatment. Findings underscore the need to train providers about risk factors and to develop interventions that increase utilisation of medical services.